2021
DOI: 10.24036/pelitaeksakta/vol4-iss2/148
|View full text |Cite
|
Sign up to set email alerts
|

A Simple Environment-Based Chemistry Lab Guide for High School Students

Abstract: This research is to create a practical guide alternative based environment forsenior high school students and determine the validity, practicality, and effectivity level of the practical guide itself. The type of this research is Research and Development (R & D). The development model used in this research is the Plomp model which consists of three phases: preliminary research, prototyping phase, and assessment phase. The research instrumentis questionnaire of validity, practicality, and effectivity sheet.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…While the average value of the practicality percentage of 3 chemistry teachers at SMAN 1 Kinali is 89.03% with a very practical category. This means that the project-based e-SW developed is easy to use, learning time is more efficient, and able to attract students' interest in learning (Sukardi, 2010) (Rochmad, 2012) and can help students find the concept of chemistry subject matter (Hardeli et al, 2021). From these practical results, the developed e-SW has been practical and can be used in learning thermochemical material by both teachers and students.…”
Section: Assessment Phasementioning
confidence: 99%
“…While the average value of the practicality percentage of 3 chemistry teachers at SMAN 1 Kinali is 89.03% with a very practical category. This means that the project-based e-SW developed is easy to use, learning time is more efficient, and able to attract students' interest in learning (Sukardi, 2010) (Rochmad, 2012) and can help students find the concept of chemistry subject matter (Hardeli et al, 2021). From these practical results, the developed e-SW has been practical and can be used in learning thermochemical material by both teachers and students.…”
Section: Assessment Phasementioning
confidence: 99%
“…The results of interviews with two chemistry teachers obtained the results of this experiment and can be used as teaching materials for students. This practicum can explain the theory of colloidal coagulation in real terms so that students become more familiar with the material (Hardeli et al, 2021). Based on the readiness and ability of teachers to carry out the experimental design, it was found that the practicum design made it easier for teachers and students to carry out the practicum.…”
Section: The Feasibility Of a Water Purification Practicum Using Tama...mentioning
confidence: 99%
“…In addition, the module is also equipped with three levels of representation in the form of colored pictures that affect the interest of students to learn it (Jalius et al, 2013). The presentation of these three levels of representation is so that students learn how to construct their knowledge from real phenomena (macroscopic level) to abstract levels (symbolic level).…”
Section: Mental Models Of Azas Le Chateliermentioning
confidence: 99%